2017
DOI: 10.1039/c6qo00515b
|View full text |Cite
|
Sign up to set email alerts
|

Calcium mediated C–F bond substitution in fluoroarenes towards C–chalcogen bond formation

Abstract: An efficient C–F bond substitution in electron-deficient fluoroarenes by chalcogens has been achieved using calcium chloride.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 89 publications
0
9
0
Order By: Relevance
“…We have developed a general and efficient method for the synthesis of bicyclic arenyl styrenyl/aryl selenides by a simple reaction of 2-naphthol and styrenyl selenocyanate/diaryl diselenide in the presence of a base at room temperature avoiding any oxidant, metal catalyst, and additive which are usually involved in reported procedures for the synthesis of selenides. To the best of our knowledge, this is the first report for the synthesis of naphthyl styrenyl selenides, which may be of potential for pharmaceutical applications. The attractive features of this methodology are high yield of product, reaction at room temperature, general applicability, and use of no metal and oxidant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have developed a general and efficient method for the synthesis of bicyclic arenyl styrenyl/aryl selenides by a simple reaction of 2-naphthol and styrenyl selenocyanate/diaryl diselenide in the presence of a base at room temperature avoiding any oxidant, metal catalyst, and additive which are usually involved in reported procedures for the synthesis of selenides. To the best of our knowledge, this is the first report for the synthesis of naphthyl styrenyl selenides, which may be of potential for pharmaceutical applications. The attractive features of this methodology are high yield of product, reaction at room temperature, general applicability, and use of no metal and oxidant.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we sought to find a protocol for selenation of a C–H bond in a bicyclic arene unit under transition metal-, oxidant-, and ligand-free condition avoiding prefunctionalization as well as introduction of a neighboring directing group. As a part of our continued program on selenation reaction, 7 we report here selenation of 2-naphthols at the 1-position through C–H bond functionalization using Cs 2 CO 3 in dimethyl sulfoxide (DMSO) at room temperature (Scheme 1). When a styrenyl selenocyanate is used as a selenating agent the corresponding naphthyl styrenyl selenide is obtained, whereas the use of diaryl diselenide provides the naphthyl aryl selenide.…”
Section: Introductionmentioning
confidence: 99%
“…Ranu et al have reported a synthesis of unsymmetrical diaryl selenides by calcium mediated aryl C–F bond substitution in activated fluoroarenes ( Scheme 13 ). 29 Many diaryl selenide compounds bearing several electron withdrawing substituents in the aromatic ring were synthesized with this method in high yields. The authors have proposed an interesting mechanism involving a transmetalation process of aryl selenide from Zn( ii ) to Ca( ii ) to produce active nucleophile Ca(SeAr) 2 .…”
Section: Under Conventional Methodsmentioning
confidence: 99%
“…Phenyl(4‐(phenylselanyl)phenyl)methanone (2d) . [ 63 ] Compound 2d (yellow oil, 84.0 mg, 83 % yield) was purified via column chromatography (PE/EA = 20:1, R f = 0.25). 1 H NMR (400 MHz, CDCl 3 ): δ = 7.77 (d, J = 7.2 Hz, 2H), 7.66 (d, J = 8.4 Hz, 2H), 7.63–7.61 (m, 2H), 7.59–7.56 (m, 1H), 7.47 (t, J = 7.8 Hz, 2H), 7.42–7.34 (m, 5H).…”
Section: Methodsmentioning
confidence: 99%
“…1 Phenyl(4-(phenylselanyl)phenyl)methanone (2d). [63] Compound 2d (yellow oil, 84.0 mg, 83 % yield) was purified via column chromatography (PE/EA = 20:1, R f = 0.25). 1 Methyl(4-(phenylselanyl)phenyl)sulfane (2f).…”
Section: -(4-(phenylselanyl)phenyl)ethan-1-one (2c)mentioning
confidence: 99%